OPTIMALISASI DESIGN SAMBUNGAN ALUMINIUM EXTRUSION 2020 MENGGUNAKAN METODE FINITE ELEMENT ANALYSIS (FEA) - Sani, Almadora Anwar; Gunawan, Indra; Fernandes, Yogi Eka; Suryana, Didi; Nugraha, Agus (Politeknik Negeri Sriwijaya, Indonesia, 2024)
With the rapid development of technology, the need for innovation is also increasing. One of the most popular technologies today is 3D printers. However, to produce quality 3D prints, a good frame structure is essential. The most important part in 3D printing is the frame structure. The most crucial part in the 3D printing process is the frame structure, namely Core XY. This is very crucial because the frame structure of the Core XY 3D printer has a big influence on the load it will accommodate in supporting the overall 3D printing process. The material used in this research is 6061 aluminum with extrusion profile 2020. This research focuses on analyzing the strength and balance of the structure, as well as the strength of the joints on the Core XY 3D printer due to static loading. To achieve this goal, researchers used the finite element analysis method using Ansys 2021 R1 software to obtain an optimal simulation. The tests used by researchers were carried out by determining the static free value that occurs in the Core XY 3D printer frame. The structural analysis results show the maximum deflection value Î´max = 0.25635mm, maximum yield stress Îµymax = 42.169 MPa, and maximum yield strain Ïƒymax = 6.1417e-004mm/mm. Researchers can conclude that the Core XY 3D printer is feasible to use to be able to produce 3D object prints.